The Impact of Communication Skills upon the Human and Social Relations among Library and Information Majors Students in the Arab World in their Point of Views - Khleel Khader, Ibrahim (Dirasat: Human and Social Sciences, 2022)
This study aimed to identify the availability of communication skills (listening, dialogue, persuasion, presentation, and body language) among the students of the communication skills course at Arab World in the academic year (2019/2020). A random sample consisting of 1000 questionnaires was distributed with 100 questionnaires to each university. (590) valid questionnaires were approved for study from the original community consisting of (a bachelor's degree among library and information science Majors students in the 10 Arab universities). The researcher used the questionnaire as a measurement tool where it consists of six areas: (Listening, dialogue, persuasion, presentation, body language, human and social relations) distributed over (54) questions, and after the collection of data was a statistical analysis to answer the questions of the study. The researcher reached through the study to several results, the most important of which are the presence of statistically significant differences in some variables at the level (α≤0.05). Less than the average of the answers of the sample respondents where it was found that there are differences with regard to sex variable and in favor of males, and no differences with university or High school and academic year, the most important recommendations reached by the researcher is to increase the credit hours of the course from 2-5 and, determine the number of students allowed In registering the course that ranges between (20-25) only, as well as increasing the practical side so that it is shared with the theoretical side.